Slope Earthquake Stability - Changwei, Yang.; Jingyu, Zhang; Jing, Lian.; Wenying, Yu.; Jianjing, Zhang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book begins with the dynamic characteristics of the covering layerbedrock type slope, containing monitoring data of the seismic array, shaking table tests, numerical analysis and theoretical derivation. Then it focuses on the landslide mechanism and assessment method. It also proposes a model that assessing the hazard area based on the field investigations. Many questions, exercises and solutions are given. Researchers and engineers in the field of Geotechnical Engineering and Anti-seismic Engineering can benefit from it.
Introduction -- Analysis of the results of the Earthquake Monitoring Array of Rock Slope in the Xishan Park during 5.12 Wenchuan Earthquake -- Shaking Table Test of Rock Slope -- Numerical Simulation of the dynamic characteristics of rock slope -- Time-Frequency analysis method of acceleration amplification of rock slope with two-side slopes -- Analysis of the deformation characteristics and landslide mechanism of the covering layer-bedrock type slope -- Time-Frequency analysis method of seismic stability of the covering layer-bedrock type slope -- Model of assessing Hazard Scope of landslide for the covering layer- bedrock type slope -- Conclusions -- Reference. .
Keywords: Engineering geology; Geotechnical engineering; Mechanics, Applied; Solids; Natural disasters; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Solid Mechanics; Natural Hazards